Settlement of Syariah Economic Dispute through the Special Court of Syariah Economic in the Religious Courts - Saut Maruli Tua Manik; Yaswirman Yaswirman; Busra Azheri; Ikhwan Ikhwan (Universitas Islam Negeri Jakarta, 2017)
The research focused on the importance of the establishment of special courts within the Religious Courts in the settlement of sharia economic disputes, and the legal construction of the establishment of a special syariah economic court within the Religious Courts. The results of research: First,the establishment of a special syariah economic court within the Religious Courts can achieve efficiency and professional realization so that the belief of sharia economic community towards the Religious Courts is realized. Second,the construction of the special law court of Islamic law within the Religious Courts is the 1945 Constitution and Law Number 48 Year 2009 on Judicial Power, and the position within the Religious Courts under the Supreme Courtin accordance with Law No. 3 of 2006 on Amendment to Law Number 7 of 1989 concerning Religious Courts jo Law Number 50 Year 2009 concerning Second Amendment to Law Number 7 Year 1989 on Religious Courts. DOI: 10.15408/ajis.v17i2.6082